Brand Avoidance Behavior in Sustainable Fashion: Insights from Generation Z Consumers - Yeshika Alversia; Natasha Syifa Hakeki (Utan Kayu Publishing, 2025)
This study aims to determine the factors that influence brand avoidance behavior in the purchase of sustainable fashion products by Generation Z in Jabodetabek. The samples used in this study were men and women with an age range of 18-26 years, domiciled in the areas of Jakarta, Bogor, Depok, Tangerang, Bekasi and had transacted or purchased fashion products. There were 236 respondents collected using a purposive sampling method. Then processed and analyzed using Partial Least Square - Structural Equation Method (PLS-SEM). This study found that sustainable fashion avoidance intention, which is influenced by ideological incompatibility, unmet expectations, and materialism, positively and significantly influences sustainable fashion avoidance behavior by Generation Z in Jabodetabek.